A clinical radiological study to evaluate the effectiveness of using a Hydroxyapatite graft mixed with injectable platelet-rich fibrin in effecting bone density in Lateral _window sinus lifting procedures - طحلاوي, زينه; خليل , عبد الكريم (Latakia University Journal -Medical Sciences Series, 2022)
This study was designed to investigate the effectiveness of using a Hydroxyapatite graft mixed with injectable platelet-rich fibrin in effecting bone density in Lateral _window sinus lifting procedures . Aim of study was to evaluate the effectiveness of using a Hydroxyapatite graft mixed with injectable platelet-rich fibrin for an ideal preparation for post-implantation . The sample included 12 patients who attended oral maxillofacial surgery department in Tishreen University Hospital and Faculty of Dentistry at Tishreen University , and the height of the remaining alveolar bone below the floor of the maxillary sinus was according to Misch classification SA-4. CBCT was performed for each patient before the surgical procedure , then they had a maxillary sinus lift with lateral window technique with bone grafting. Density of new bone formed was evaluated at 4 and 6 months after surgery . The average bone density before surgery was 700.22 , while after 4 months it was 591,31, and after 6 months it was 617.14 . Conclusion : Injectable platelet-rich fibrin mixed with Hydroxyapatite graft was shown to increase the speed of bone healing and thus reduce the time between grafting and implantation .